Novel Strategies in Hematopoietic Stem Cell Transplantation - Emmanouil Magiorkinis (Annals of Bone Marrow Research - Peertechz Publications, 2016)
Hematopoietic stem cell transplantation (HSCT) is an important life-saving procedure which is applied in cases of genetic defects or malignant tumors. Hematopoietic stem cells (HSCs), reside in certain "niches" within the bone marrow allowing them to reproduce themselves and remain in undifferentiated state [1,2], whereas there are evidence that HSC population is not homogenous and can be divided into subtypes [2]. Dependent on the donor of HSC, HSCT can be autologous (if the donor and the recipient is the same person), allogeneic (HSC come from a different person) or syngeneic (HSC donor is identical twin).